Full Response of a Localized Renal Tumour after Reduced-Intensity Conditioned Hematopoietic Stem Cell Transplantation. (19th October 2009) - Gac, Anne-Claire; Chantepie, Sylvain; Leporrier, Michel; Reman, Oumedaly
Abstract : Graft versus tumor effect has been described in solid metastatic tumor. We reported here the case of a patient treated for an acute myeloid leukemia with reduced-intensity conditioned allograft and the effect of this procedure on concomitant of renal localised cancer. The effect of immune-mediated cytotoxicity on renal cancer is the more consistent explanation to understand the necrosis of this tumor. Any case of RIC allograft has been reported before to treat localised renal tumor.